Elm (Ulmus) leaf miners in North-East Kazakhstan - M. Zhussip; K. Akhmetov; U. Burkitbaeva (Biosystems Diversity, 2023)
Leaf miners are increasingly causing damage to plants, often causing their death. There are about 10 thousand species of leaf miners in the world. The purpose of this study is to establish the location, species diversity, as well as the degree of damage caused by leaf miners to the leaves of Ulmus L. genus trees in the Pavlodar Region. In the course of the study, a visual inspection of the affected areas was used, as well as the selection, drying of damaged foliage and, subsequently, the removal of larvae and adult insects from it, followed by their study. During the vegetation seasons in 2019–2022, in Pavlodar, Ekibastuz and Aksu cities, as well as in Zhelezinka and Koktobe villages, elm leaves were studied for the presence of leaf miners, a visual inspection of the damage locations was conducted, and samples were taken, which later became the material for growing and detailed study of insects at different development stages. The article considers phyllophagous insects mining elm leaves in the North-East of Kazakhstan (Pavlodar Region) in 2019–2022. In the course of the conducted studies on the territory of the Pavlodar Region, 8 species belonging to 5 genera were identified: Stigmella Schrank, 1802, Orchestes Illiger, 1798, Fenusa Leach, 1817, Bucculatrix Zeller, 1839 and Phyllonorycter Hubner, 1822. Leaf miners that belong to the Agromyza genus of the Agromyzidae family were also identified. All representatives are obligate leaf miners, developing at the larval stage in the mesophyll of elm leaves. Most of the leaf-mining insects are represented by Agromyza and Stigmella species. They are among the most dangerous for the biocoenosis of the Pavlodar Region. Moreover, Agromyza insects have high plasticity and may become a problem in other regions. The obtained data will help to contribute to further studies in this direction, and also show the development degree of an understudied problem: the influence of leaf miners on the nature of Kazakhstan.